What Drives Employee's Involvement and Turnover Intentions: Empirical Investigation of Factors Influencing Employee Involvement and Turnover Intentions? - Alshammari, Marwan Ahmad; AL Qaied, Bader Ayed; Al-Mawali, Hamzah; Matalqa, Mohammad (International Review of Management and Marketing, 2016)
Research findings on job involvement and turnover intentions have been somewhat mixed. Scholars have often studied job involvement as an antecedent of some employee and organization outcomes, including job satisfaction and turnover. The present study examines the antecedents of job involvement and factors influencing it. Namely, organizational attractiveness, pay satisfaction, and organizational support. I also examine the effects of job satisfaction, job involvement, person-organization fit, and organizational support on turnover intentions and whether mediation mechanisms exist underlying the relationships between these constructs and turnover intentions. The analysis yielded mixed results for both constructs, involvement and turnover; suggesting further studies might be necessary, and that incorporating more intervening variables might help improve our understanding of the interrelationships between these constructs. Results are discussed and future research directions are suggested. Keywords: job satisfaction, pay satisfaction, turnover intention, structural equation modeling. JEL Classification: J28